Smoking cessation policy and treatments derived from the protective motivation of smokers: a study on graphic health warning labels - Pang, Qiwei; Wang, Lu; Yao, Jinge; Yuen, Kum Fai; Su, Miao; Fang, Mingjie (Frontiers in Psychology, 2023)
Smoking is a leading public health risk. Many countries are reducing the demand for tobacco through graphic health warning labels (GHWLs). This study aims to explore smokers’ perceptions of GHWLs and analyze the effect of GHWLs on their behavioral intentions to quit smoking. A theoretical model is designed by synthesizing protection motivation theory, an extension of the extended parallel process model, and the theory of planned behavior. We collected a cross-sectional sample of 547 anonymous smokers through a stratified random sampling strategy. GHWLs published in 2011 by the US Food and Drug Administration were used in the survey to assess smokers’ responses to them, and then the hypotheses are validated through structural equation models. The results suggest that perceived severity, perceived vulnerability, response efficacy, and health anxiety have a significant impact on smokers’ protection motivation. Consequently, smokers’ protection motivation directly impacts the behavioral intention to quit smoking and indirectly influences intention to quit through attitudes. These findings have practical implications for the implementation and improvement of GHWLs policies.